DEVELOPING ESP TEACHING MATERIALS FOR THE STUDENTS OFTHE SOFTWAREENGINEERINGBASED ON PROBLEM BASED LEARNING AT THE AL-WASHLIYAHTELADAN VOCATIONAL SCHOOL - Hasibuan, Rodiani Fatmah; Gurning, Busmin; Setia, Eddy (TABULARASA, 2015)
This study dealt with the development of English Reading Materials of vocational school, Al-WashliyahTeladan Medan, majoring Software Engineering. The objectives of this study were to: 1) find out language skill and materials are needed by the students of Software Engineering, 2) develop the English materials for the majoring in software engineering students at the vocational high school grade XII. This study was conducted by Educational Research and Development R&D (Borg & Gall, 1989). The data of this research were from existing documents and the result of interview with teacher and student. The results of the research conveyed that the existing reading materials were mostly irrelevant because the title and content of the material was not appropriate and was not required for the students majoring in software engineering. The new English reading materials and syllabus were developed based on the students need related to the workplace. The materials and syllabus were developed from the existing materials from teacher. The developing materials were validated by two experts.